Elizabeth Bishop's poetics of description - Pickard, Zachariah, 1976- (McGill-Queen's University Press, 2009)
Many readers are struck by Elizabeth Bishop's use of clear, striking descriptions of the physical world, and no scholar has ever asked how Bishop's commitment to description shapes her writing and thinking.